Natural and engineered production of taxadiene with taxadiene synthase. Issue 2 (21st October 2014) - Soliman, Sameh; Tang, Yi
ABSTRACT Taxadiene synthase (TXS) is the rate‐limiting enzyme in the biosynthesis of paclitaxel, an important anticancer compound. TXS catalyzes the conversion of the diterpene precursor geranylgeranyl pyrophosphate (GGPP) into the diterpene taxadiene. Due to the importance of taxadiene in the overall biosynthetic pathway of paclitaxel biosynthesis, the enzyme TXS has been the subject of intense scientific and engineering investigations. The crystal structure of TXS was recently elucidated, thereby providing an atomic blueprint for future protein engineering efforts. Metabolic engineering of TXS for taxadiene product in different microbial and plant organisms have also been extensively performed, culminating in the high‐titer production in Escherichia coli. Additional aspects of taxadiene production by TXS will be discussed in the review, including metabolic regulation in native host and possible production by endophytic fungal hosts. Biotechnol. Bioeng. 2015;112: 229–235. © 2014 Wiley Periodicals, Inc.